(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of primiparous women and the indications for cesarean section at Thai Binh Obstetrics and Gynecology Hospital during the first six months of 2025. Subjects and methods: The study was conducted on 395 primiparous women undergoing cesarean section at Thai Binh Obstetrics and Gynecology Hospital from January 1st to June 30th, 2025, using a descriptive cross-sectional and prospective study design. Results: Cesarean section for first-time mothers was most common at an average age of 28.5 ± 3.03; with no history of infertility (69.4%); no miscarriage (76.2%); with reproductive organ pathology (5.1%); carrying twins (2%); breech, shoulder, face, and brow presentation (19%); fetal malformations (0.3%) and fetal distress (15.9%); and fetal weight > 4000g accounted for 5%. The majority of cesarean sections had ≥ 2 indications (62.5%), including causes related to the fetal adnexa (65.3%), fetal causes (48.6%), labor abnormalities (46.3%), maternal genital tract issues (41.3%), and maternal pathology (35.4%). Cesarean sections due to social causes and other issues accounted for 34.9%. Regarding fetuses, the gestational age group of 38-41 weeks accounted for the highest percentage (88.1%). Conclusion: Cesarean sections for first-time mothers at Thai Binh Obstetrics and Gynecology Hospital are performed due to reasons related to the mother, the fetus, and societal factors.